2022
DOI: 10.3346/jkms.2022.37.e214
|View full text |Cite
|
Sign up to set email alerts
|

Designing Infographics: Visual Representations for Enhancing Education, Communication, and Scientific Research

Abstract: Infographics are graphic visual representations of educational content, used to deliver complex information, disseminate scientific research, and drive behavioral change. Herein, we review some of the factors pertinent to designing infographics and the potential for automation in the future. To guide high-impact design, it is vital to clearly define the objectives of the infographic and its target audience. Designing an effective infographic necessitates careful consideration of the layout, colors, font, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…This means that the developed infographic content meets very high acceptability elements. Infographics are a visual way of presenting detailed research results, data, and information [23]. The developed infographics meet the elements of conveying more detailed data information so that training participants can receive information accurately.…”
Section: Resultsmentioning
confidence: 99%
“…This means that the developed infographic content meets very high acceptability elements. Infographics are a visual way of presenting detailed research results, data, and information [23]. The developed infographics meet the elements of conveying more detailed data information so that training participants can receive information accurately.…”
Section: Resultsmentioning
confidence: 99%
“…Infographics are a flexible medium where instructors can use their knowledge to boost student learning, and involving students in their development could replace traditional teaching/learning techniques with more active and innovative ones (Chicca & Chunta, 2020). This point of view has been supported even further by Traboco et al (2022) who found that infographics can be used to facilitate teaching and learning in many ways, and infographics can improve learning, memory, recall, comprehension, and communication skills. Infographics assist teachers in turning complex content into engaging, aesthetically appealing knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Infographics might be used in varied ways and for a number of educational purposes, especially for facilitating teaching and learning activities. As a teaching tool, infographics enhance engagement, memory retention, recall, comprehension, and the development of communication skills (Traboco et al, 2022). Infographics can help educators transform complicated material into more easily digested, engaging, and visually appealing information.…”
Section: Facilitating Teaching and Learningmentioning
confidence: 99%
“…An infographic is a visual composition of text and images with the potential to convey messages in a concise and practical way without compromising their scientific value. Thus, infographics may constitute an effective educational resource [ 11 ] for transmitting complete messages [ 12 ] and driving behavioural change [ 13 ]. In an infographic, image and text are usually complementary; when the image fails to convey the message, the text fulfils this function, and vice versa.…”
Section: Introductionmentioning
confidence: 99%